PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN PADA DESA PANDAMAAN KECAMATAN DANAU PANGGANG KABUPATEN HULU SUNGAI UTARA - Arief Budiman; Sugianor Sugianor (Jurnal PubBis, 2018)
Community participation has many forms, ranging from direct community participation in government programs and indirect ones, such as donations of funds, energy, thoughts, and opinions in government policy making. The success of the implementation of village development depends largely on the role of the government and the community. But in reality the level of Community Participation for the Development of Pandamaan Village, Danau Panggang Subdistrict at the socialization stage and until the implementation stage of infrastructure development activities is still relatively low. The research method used in this study is a qualitative descriptive method in which data collection techniques using observation, interviews or interviews, and documentation with the number of informants as many as 20 people in Pandamaan Village, Danau Panggang District, Hulu Sungai Utara District. Based on the results of the research, Community Participation in Development In Pandamaan Village, Danau Panggang Subdistrict, Hulu Sungai Utara District was still relatively low, seen from community participation in mental and emotional involvement, not involved in the involvement of giving ideas, roles or motivation, encouragement to contribute, in the form of material (money), energy, or facilities, considered to be non-existent. in terms of accepting responsibility, including in the utilization of results and maintenance of development results, considered fair, in planning and decisions, determining the location of the community helped, the community was not involved to become labor because of lack of expertise, in the implementation stage the community was less concerned, there was no supervision and evaluation from the community and for the utilization of results related to the data collection and the establishment of a community development maintenance group does not matter. Keywords: Community Participation; Development